P38 Mitogen-Activated Protein Kinase Protects Against Retinoblastoma Through Regulating USP22/SIRT1/SOST Axis - Huang, Xiaoming; Wan, Jianfeng; Liu, Fei; Liu, Yang; Wang, Lina; Zhao, Sidi; Wu, Tong; Sun, Fengyuan (Frontiers in Oncology, 2022)
Retinoblastoma (RB) is the most common intraocular malignancy in children. It has been previously reported that p38 MAPK is related to the pathogenesis of RB. Here we aims at investigating how p38 MAPK affected RB progression through mediating USP22/SIRT1/SOST axis. In this study, Thirty-two cases of RB and normal retinal tissues were collected. The expression of p38 MAPK, phosphorylation of p38 MAPK (P-p38 MAPK), USP22, SIRT1 and SOST in clinical tissues and cells was measured using RT-qPCR, IHC assay or western blot analysis. Cell proliferation was detected by CCK-8. Apoptosis rate of cells was examined by flow cytometry. Cell migration was evaluated using scratch test. Cell invasion ability was examined by Transwell assay. Co-immunoprecipitation (CO-IP) was utilized to measure the deubiquitination of USP22 on SIRT1. In vivo, mice were respectively injected with plasmids and the tumor growth as well as the tumor weight were detected. Results showed that p38 MAPK, P-p38 MAPK and SOST were poorly expressed in RB tissues and cells whereas USP22 and SIRT1 were overly expressed. P-p38 MAPK inhibited the expression of USP22, and overexpression of USP22 eliminated the inhibitory roles of P-p38 MAPK on tumor growth, as well as cell proliferation, migration and invasion. USP22 stabilized and promoted the expression of SIRT1 through its deubiquitination function. Silencing the expression of SIRT1 contributed to boosted expression of SOST, thus suppressing the growth of tumor cells. Collectively, the phosphorylation of p38 MAPK regulates the SIRT1/SOST axis to protect against RB via silencing USP22. The findings present some cues for a further approach to RB.